Performance Allowance and Work Environment as Determinants of Employee Performance in the Public Sector: Evidence from Merauke Regency. (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study examines the effects of performance allowances and work environment on employee performance at the Regional Secretariat of Merauke Regency, Indonesia. The research was motivated by the need to enhance public sector productivity through effective human resource management in a decentralized administrative context. Using a quantitative explanatory design, data were collected from 129 civil servants selected through purposive sampling. Data analysis employed multiple linear regression using IBM SPSS Statistics 26. The findings reveal that both performance allowances and the work environment significantly and positively influence employee performance, both individually and simultaneously. Performance allowances function as extrinsic motivators that enhance accountability and work enthusiasm, whereas a supportive work environment strengthens psychological comfort, collaboration, and commitment. Among the two factors, the work environment demonstrated a stronger influence, underscoring the importance of non-financial determinants in sustaining performance. The study concludes that a synergistic combination of fair compensation policies and conducive workplace conditions is essential for optimizing employee performance in public organizations. Practical implications include policy reform in allowance structures, workplace modernization, and integrated capacity development strategies.